(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The world where we live has been undergone different periods characterized by the level of development of humankind and his capabilities to make life much better for himself. A man learnt how to start a fire, invented a wheel, built a house and left caves, and today he is totally delegating all the tasks to his new invention, called an artificial intelligent (AI) that would complete them on high quality. We have already turned from the era of computers into the AI period of development which means that there are new requirements for the translators in this sphere. However, there are appearing several errors in translation process of technical texts that need to be corrected by thoroughly studying the nature of technical language of source and target languages. The actuality of this work is due to the increasing importance of translation of scientific and technical literature as a way of exchanging and disseminating information in the global scientific community.